Challenges of mastering the energy sector and sustainable solutions for development in Africa - (:unkn) unknown (My University, 2019)
The African continent is currently experiencing a period of sustained economic and population growth that requires massive investment in the energy sector to effectively meet the energy needs in the context of sustainable development. At the same time, COP21 agreements now call all the states to use clean energy. Yet a great energy potential is available, but the electrification rate of the continent currently accounts for only 3% of the world's energy production. Also, the demand for both quality and quantity energy requires the mastery of applied mathematical tools to efficiently solve problems arising in the energy system. In this article, the major problems affecting the energy sector in Africa are identified, some solutions to the challenges are recalled and some new ones are proposed, with emphasis given to applied mathematics tools as well as energy policy. As case studied, a new control strategy of Static Synchronous Series Compensator (SSSC) devices-which are modern power quality Flexible Alternating Current Transmission Systems (FACTS)-is proposed for Power Flow Control.
Keywords: African Research